How do users respond to online rumor rebuttals? - Pal, Anjan (2022)
Underpinned by the Stimulus-Organism-Response framework and the anchoring effect, this paper investigates how perceived message properties of online rumor rebuttals are related to perceived utilitarian and hedonic values, which further could determine rebuttal acceptance. Given the possibility that Internet users can confront a rebuttal when they are not even aware of the rumor, this paper takes into account the role of exposure sequence as a moderator. Data were collected from 322 social media users in a between-participants experiment, which manipulated the exposure sequence. Partial least squares structural equation modeling was used to analyze the data. Perceived message properties were positively associated with perceived utilitarian and hedonic values, both of which were positively related to rebuttal acceptance. Exposure sequence significantly moderated the underlying mechanism of rebuttal acceptance. This paper contributes to the online rebuttal literature by examining how individuals respond to rebuttals in terms of intention to believe and share such messages. It also has implications for practitioners and other Internet users.